Computational discovery of a new rhombohedral diamond phase - Li, Zhen-Zhen; Wang, Jian-Tao; Mizuseki, Hiroshi; Chen, Changfeng (AMER PHYSICAL SOC, 2018)
We identify by first-principles calculations a new diamond phase in R (3) over bar (D-3d(6)) symmetry, which has a 16-atom rhombohedral primitive cell, thus termed R16 carbon. This rhombohedral diamond comprises a characteristic all-sp(3) six-membered-ring bonding network, and it is energetically more stable than previously identified diamondlike six-membered-ring bonded BC8 and BC12 carbon phases. A phonon mode analysis verifies the dynamic structural stability of R16 carbon, and electronic band calculations reveal that it is an insulator with a direct band gap of 4.45 eV. Simulated x-ray diffraction patterns provide an excellent match to recently reported distinct diffraction peaks found in milled fullerene soot, suggesting a viable experimental synthesis route. These findings pave the way for further exploration of this new diamond phase and its outstanding properties.
Keywords: HIGH-PRESSURE; MOLECULAR-DYNAMICS; CARBON ALLOTROPES; SILICON; FORMS; STATE